Analysis of Factors Hindering Artificial Intelligence Adoption in Office Management among Generation Z Interns - Paramita, Happy; Effendi, Muhammad Rizky (International Journal Administration, Business & Organization, 2025)
Generation Z enters the workforce as digital natives with high technological proficiency, yet a significant gap exists between their digital potential and actual Artificial Intelligence (AI) utilization in traditional office settings. The purpose of this research is to analyze this paradox of AI adoption among Generation Z interns in office management contexts. Although this generation is considered highly tech-savvy, preliminary observations indicate a lack of AI utilization in their internship roles. This study aims to investigate the structural, cultural, and task-related barriers that prevent them from effectively leveraging AI. This study employs a qualitative method involving in-depth interviews with eight subjects from various companies in Bandung, supported by relevant literature. The findings reveal that the low adoption of AI is primarily driven by three critical factors: (1) structural barriers, specifically the mandatory use of legacy systems and strict data security policies; (2) cultural barriers, such as hierarchical environments that suppress autonomy; and (3) task-related barriers, where repetitive clerical tasks are deemed incompatible with generative AI capabilities. Through the lens of Task-Technology Fit (TTF) and Technology Acceptance Model (TAM), the analysis demonstrates that high digital literacy does not guarantee adoption when organizational infrastructure barriers exist. The results underscore the urgent need for organizations to modernize their infrastructure and redefine internship roles to fully harness the potential of the Gen Z workforce.